Model Pembiayaan Syariah Berbasis Teknologi dalam Mendukung Pengembangan Industri Halal - Lili Puspita Sari; Ade Nur Rohim; Prima Dwi Priyatno (Jurnal Ilmiah Ekonomi Islam, 2023)
The technology-based Islamic financing model is growing in line with the presence of Islamic fintech institutions in Indonesia.. This is accompanied by the large potential of the national halal industry. This study aims to examine alternative financing models for Islamic fintech institutions in Indonesia in supporting the development of the halal industry through MSME business actors.The results of the study explain several alternative contracts that can be optimized to support the development of innovative sharia fintech financing models, such as IMBT, MMQ and Waqf. On the other hand, the development of a financing model also needs to be supported by the integration of financing platforms with related institutions and institutions to support the role and development of sharia fintech and the halal industry ecosystem in Indonesia.